2019
DOI: 10.5194/amt-12-3825-2019
|View full text |Cite
|
Sign up to set email alerts
|

Method to retrieve cloud condensation nuclei number concentrations using lidar measurements

Abstract: Abstract. Determination of cloud condensation nuclei (CCN) number concentrations at cloud base is important to constrain aerosol–cloud interactions. A new method to retrieve CCN number concentrations using backscatter and extinction profiles from multiwavelength Raman lidars is proposed. The method implements hygroscopic enhancements of backscatter and extinction with relative humidity to derive dry backscatter and extinction and humidogram parameters. Humidogram parameters, Ångström exponents, and lidar extin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…If only data with an FMF above 0.6 are considered (blue dots in Figure ), a valid relationship can be found between δ p and the rebound fraction. It has been reported that the backscatter properties at 532 nm contain mainly information for large particles (over 60% of information is contributed by particles with dry diameters greater than 400 nm, and over 80% is contributed by particles with dry diameters greater than 300 nm). Therefore, we examined only the relationship between δ p and the rebound fraction for 400 nm particles.…”
Section: Resultsmentioning
confidence: 99%
“…If only data with an FMF above 0.6 are considered (blue dots in Figure ), a valid relationship can be found between δ p and the rebound fraction. It has been reported that the backscatter properties at 532 nm contain mainly information for large particles (over 60% of information is contributed by particles with dry diameters greater than 400 nm, and over 80% is contributed by particles with dry diameters greater than 300 nm). Therefore, we examined only the relationship between δ p and the rebound fraction for 400 nm particles.…”
Section: Resultsmentioning
confidence: 99%
“…The relationships between particle extinction coefficients and number concentrations of particles with a dry radius larger than 50 nm (for non-dust) and 100 nm (for dust) were parameterized based on multiyear AERONET observations for different aerosol types. However, the measurements from the single wavelength lidar also lack sufficient information to quantify particle size distribution, particle number concentration or aerosol type, resulting in large uncertainty in NCCN retrieval (Burton et al, 2012;Tan et al, 2019). However, few recent studies (Lv et al, 2018;Tan et al, 2019) have shown efforts to retrieve NCCN based on the advanced capability of multiwavelength lidar measurements, but they have been limited to ground-based observations only.…”
Section: Introductionmentioning
confidence: 99%
“…However, the measurements from the single wavelength lidar also lack sufficient information to quantify particle size distribution, particle number concentration or aerosol type, resulting in large uncertainty in NCCN retrieval (Burton et al, 2012;Tan et al, 2019). However, few recent studies (Lv et al, 2018;Tan et al, 2019) have shown efforts to retrieve NCCN based on the advanced capability of multiwavelength lidar measurements, but they have been limited to ground-based observations only. Rosenfeld et al, (2016) have attempted a new approach to retrieve satellite based NCCN using passive satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the optical and microphysical properties of water clouds affect their capability to absorb and scatter radiation, and this poses a major challenge leading to uncertainty in numerical weather forecasts and climate simulations [2,3]. Testing and improving parameterization schemes for cloud variations and physical processes requires knowledge of cloud properties [4,5]. Hence, the current techniques will be validated and new ones will be developed for retrieving water properties.…”
Section: Introductionmentioning
confidence: 99%